Secondary metabolites of Pinus halepensis alter decomposer organisms and litter decomposition during afforestation of abandoned agricultural zones. (8th January 2014) - Chomel, Mathilde; Fernandez, Catherine; Bousquet‐Mélou, Anne; Gers, Charles; Monnier, Yogan; Santonja, Mathieu; Gauquelin, Thierry; Gros, Raphael; Lecareux, Caroline; Baldy, Virginie; Austin, Amy
Summary Over a century of agricultural abandonment across the Mediterranean region has favoured the installation of the pioneer expansionist species Aleppo pine (Pinus halepensis Miller). This species synthesizes a wide range of secondary metabolites that are partially released during needle decomposition, and which can thus affect the 'brown food chain'. Litter decomposition is a key process connecting ecosystem structure and function, and involving microbial and faunal components. The goal of this study was to determine the effect of chemical compounds from Aleppo pine needles on the litter decomposition process along a gradient of Mediterranean forest secondary succession. Using in situ litterbags, we compared the dynamics of decomposers, particularly the relative contributions of fungal and mesofauna biomass to litter mass loss (calculations based on the measured decomposer biomass, published fungal growth efficiency and mesofauna feeding rate), against the dynamics of secondary metabolites associated with decomposed needles in three successional stages (early, middle and late, i.e. pinewoods that were aged 10, 30 and over 60 years old). Our first key finding was that fungi accounted for the largest portion of overall litter mass loss (60–79%) and detritivorous mesofauna contributed to 8–12%. In the early stage of succession, fungal biomass after 6 months of decomposition was lower than in middle and late stages, and may be responsible for the delay in litter colonization by mesofauna. We linked this result to a clearly longer residence time for phenolic compounds in young pine forest, leading to an overall slowdown in the decomposition process. Synthesis. Litter phenolic content emerged as a key functional trait for predicting litter decomposition, delaying the colonization of litter by decomposers in Mediterranean forest ecosystems. Another key finding is that the relative contributions of fungi and detritivores to needle mass loss were different between the successional stages. From the food‐web perspective, the organic matter available for higher trophic levels thus remains unchanged beyond 30 years after pine colonization.